Eight Years Of Journal Of Muamalat And Islamic Finance Research (JMIFR) (2004-2011) : A Way Forward - Fuadah Johari; Muhammad Ridhwan; Muhammad Mohamad Yusoff (DigitalCommons@University of Nebraska - Lincoln, 2024)
Library Philosophy and Practice (e-journal)